2017
DOI: 10.1021/acs.jnatprod.6b00915
|View full text |Cite
|
Sign up to set email alerts
|

Tannins and Tannin-Related Derivatives Enhance the (Pseudo-)Halogenating Activity of Lactoperoxidase

Abstract: Several hydrolyzable tannins, proanthocyanidins, tannin derivatives, and a tannin-rich plant extract of tormentil rhizome were tested for their potential to regenerate the (pseudo-)halogenating activity, i.e., the oxidation of SCN to hypothiocyanite OSCN, of lactoperoxidase (LPO) after hydrogen peroxide-mediated enzyme inactivation. Measurements were performed using 5-thio-2-nitrobenzoic acid in the presence of tannins and related substances in order to determine kinetic parameters and to trace the LPO-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…An ethanolic extract of Tormentil and some other compounds such as ellagic acid or methyl gallate were found as potent LPO-enzyme-regenerating compounds. These results may provide a further reason for the application of Tormentil extract, which is known for its antibacterial and anti-inflammatory, as well as plaque inhibiting, effects in the mouth [35]. In addition, the Tormentil extract processed in mucoadhesive dosage forms was able to significantly reduce artificial biofilm formation by cariogenic Streptococcus mutans in a porcine buccal mucosa model in vitro.…”
Section: Hydrolysable Tanninsmentioning
confidence: 73%
“…An ethanolic extract of Tormentil and some other compounds such as ellagic acid or methyl gallate were found as potent LPO-enzyme-regenerating compounds. These results may provide a further reason for the application of Tormentil extract, which is known for its antibacterial and anti-inflammatory, as well as plaque inhibiting, effects in the mouth [35]. In addition, the Tormentil extract processed in mucoadhesive dosage forms was able to significantly reduce artificial biofilm formation by cariogenic Streptococcus mutans in a porcine buccal mucosa model in vitro.…”
Section: Hydrolysable Tanninsmentioning
confidence: 73%
“…Hydrogen peroxide concentration in saliva equals to 8–13 μM under physiological conditions [76], and increases several fold in inflammatory diseases of the mouth [77]. Its production is ensured by both oral microorganisms as well as by the cells and enzymatic systems of the host [18], while bacterial production is sufficient to ensure the proper functioning of the salivary lactoperoxidase system.…”
Section: Substrates—availability and Importancementioning
confidence: 99%
“…Reactivators include many substances of natural origin belonging to flavonoids [111], polyphenols [29], tannins [77], and cinnamic acid derivatives [112]; moreover, there are ongoing studies on the use of plant extracts containing more than one substance with such an effect [113,114]. In addition to the direct bactericidal action, Flemmig et al showed the reactivating properties of some components of the Olea europaea extract on LPO Compound II [113].…”
Section: Chemical Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, that in the course of inflammatory diseases of the oral cavity, such as dental caries or gingivitis, the synthesis of hydrogen peroxide is increased due to intensified oxidative phenomena [ 19 ]. This leads to the intensification of Compound I synthesis and imbalance between excretion of SCN – ions and its oxidation by Compound I.…”
Section: Introductionmentioning
confidence: 99%